ARTIFICIAL INTELLIGENCE TOOLS IN FOREIGN LANGUAGE TEACHING IN HIGHER EDUCATION INSTITUTIONS - Юніна, Ольга Євгенівна (The Modern Higher Education Review, 2025)
The article is devoted to the problem of using artificial intelligence (AI) tools in the system of teaching foreign languages in higher education institutions. The study includes an overview of modern approaches to language teaching, the advantages, and possibilities of using AI in the educational process, as well as an analysis of the impact of these tools on the academic achievements of students. The objectives of the research are as follows: to determine the effectiveness and impact of artificial intelligence tools on the process of teaching foreign languages in higher education institutions, and to identify the most productive pedagogical strategies for integrating AI tools into foreign language instruction. The importance of integrating artificial intelligence into the process of teaching foreign languages is substantiated, and the potential benefits for students and teachers are highlighted. Some interactive language programs and learning platforms that allow students to practice a foreign language in virtual situations, and receive feedback are analyzed. The use of artificial intelligence makes it possible to create adaptive learning platforms that individually adjust to the needs and abilities of each learner. Particular attention is paid to the possibility of individualizing the learning process through artificial intelligence, which allows students to learn a foreign language according to their needs and pace. The use of AI makes it possible to identify the optimal teaching methods for each student based on their individual abilities, learning styles, and interests. This individualized approach to learning helps learners master the material more effectively, ensures maximum adaptation to their needs, and provides more successful results in learning foreign languages. Some of the risks of using AI in the educational process are identified, including the risk of turning language learning into a mechanical process without taking into account the context and cultural characteristics. The need to ensure system resilience and data security is emphasized, as a large amount of information that may relate to the personal data of students can be stored in AI systems. Based on the studied data and analysis, conclusions are drawn about the prospects for integrating artificial intelligence into foreign language teaching. It is noted that the use of artificial intelligence tools in foreign language teaching may prove to be a promising tool for improving the educational process, which will ensure more effective learning in the future.